Surface fluxes over Goa during Indian monsoon (MAUSAM, 2005)
Variation of surface sensible heat flux over the west coast in the premises of National Center for Antarctic and Ocean Research (NCAOR), Vasco-da-Gama (15° 21' N, 73° 51' E), Goa during Offshore trough (phase-I) and Warm pool campaigns (phase-II) of ARMEX is studied. Sensible heat flux as measured by sonic anemometer at 5 m above surface is -50 to 150 Wm-2 during 13-28 July, 2002 (phase I) and -5 to 350 Wm-2 during 21-24 April, 2003 (phase II). Coastal atmospheric surface layer at Goa during night time is found to be near neutral (nearly zero heat flux) in April 2003 whereas stable (negative heat flux) in July 2002. All components of solar radiation measured by Eppley radiometers at 2 m above surface are used to compute net radiation which is 900 Wm-2 at noon in April 2003. Net solar radiation is nearly equal to incoming short wave radiation during daytime as net long wave radiation (100 Wm-2) compensates the loss due to reflection of short wave radiation (-100 Wm-2) by the ground. High winds in the surface layer are observed during late night hours with calm winds around sunrise and after sunset giving rise to two minima in the diurnal curve. Influence of sea-breeze on the surface layer over land is discussed.